Rhodium-Catalyzed Intermolecular Reaction of Alkyl Azides with Diazo(aryl)acetates - Gu, Peiming; Wu, Xiu-Ping; Su, Yan; Li, Xue-Qiang; Xue, Ping; Li, Rui (Synlett, 2014)
An efficient intermolecular interception of alkyl azides by diazo(aryl)acetates was achieved in the presence of dirhodium tetraoctanoate. The initial products were unstable α-imino esters, and overaddition of carbenoids to the C–N double bonds was avoided. After acidic workup, the corresponding α-keto esters were obtained in good to excellent yields.
Keywords: azides; carbenoids; diazo compounds; imines; esters; catalysis; rhodium